Quantifying resilience to flooding among households and local government units using system dynamics: a case study in Metro Manila. Issue 3 (10th December 2015) - Gotangco, C.K.; See, J.; Dalupang, J.P.; Ortiz, M.; Porio, E.; Narisma, G.; Yulo‐Loyzaga, A.; Dator‐Bercilla, J.
Abstract: A generic systems dynamics (SD) model template for resilience is adapted to analyse flooding impacts on household assets and local government assets of Pasig City, Metro Manila. SD simulations are used to quantify the loss of system performance due to adverse impacts, and the recovery of the system due to response measures. The simulation results reflect the decreasing levels of resilience among low‐income households, and the reliance of local government on budgeting cycles to replenish assets. The initial model needs to be expanded to include other determinants of resilience, but this exploratory study reflects the potential usefulness of SD simulations as a decision support tool for city policy makers. By quantifying changes in resilience measures over time, simulations can complement qualitative analyses and test policy and programme scenarios.